Current and Emerging Azole Antifungal Agents - Sheehan, Daniel J. (American Society for Microbiology, 1999)
Major developments in research into the azole class of antifungal agents during the 1990s have provided expanded options for the treatment of many opportunistic and endemic fungal infections. Fluconazole and itraconazole have proved to be safer than both amphotericin B and ketoconazole. Despite these advances, serious fungal infections remain difficult to treat, and resistance to the available drugs is emerging. This review describes present and future uses of the currently available azole antifungal agents in the treatment of systemic and superficial fungal infections and provides a brief overview of the current status of in vitro susceptibility testing and the growing problem of clinical resistance to the azoles. Use of the currently available azoles in combination with other antifungal agents with different mechanisms of action is likely to provide enhanced efficacy. Detailed information on some of the second-generation triazoles being developed to provide extended coverage of opportunistic, endemic, and emerging fungal pathogens, as well as those in which resistance to older agents is becoming problematic, is provided.